Infections in relapsed myeloma patients treated with isatuximab plus pomalidomide and dexamethasone during the COVID-19 pandemic: Initial results of a UK-wide real-world study. Issue 1 (31st December 2022) - Djebbari, Faouzi; Rampotas, Alexandros; Vallance, Grant; Panitsas, Fotios; Basker, Nanda; Sangha, Gina; Salhan, Beena; Karim, Farheen; Firas, Al-Kaisi; Gudger, Amy; Ngu, Loretta; Poynton, Matt; et al.
ABSTRACT: Objectives: There are no real-world data describing infection morbidity in relapsed/refractory myeloma (RRMM) patients treated with anti-CD38 isatuximab in combination with pomalidomide and dexamethasone (IsaPomDex). In this UK-wide retrospective study, we set out to evaluate infections experienced by routine care patients who received this novel therapy across 24 cancer centres during the COVID-19 pandemic. Methods: The primary endpoint was infection morbidity (incidence, grading, hospitalization) as well as infection-related deaths. Secondary outcomes were clinical predictors of increased incidence of any grade (G2–5) and high grade (≥G3) infections. Results: In a total cohort of 107 patients who received a median (IQR) of 4 cycles (2–8), 23.4% of patients experienced ≥1 any grade (G2–5) infections (total of 31 episodes) and 18.7% of patients experienced ≥1 high grade (≥G3) infections (total of 22 episodes). Median time (IQR) from start of therapy to first episode was 29 days (16–75). Six patients experienced COVID-19 infection, of whom 5 were not vaccinated and 1 was fully vaccinated. The cumulative duration of infection-related hospitalizations was 159 days. The multivariate (MVA) Poisson Regression analysis demonstrated that a higher co-morbidity burden with Charlson Co-morbidity Index (CCI) score ≥4 (incidence rate ratio (IRR) = 3, p = 0.012) and sub-optimal myeloma response less than a partial response (<PR) ( p = 0.048) are independent predictors of ≥ G3 infections. Conclusion: Our study described initial results of infection burden during IsaPomDex treatment. We recommend close monitoring particularly in elderly patients with co-morbidities, the effective use of an-infective prophylaxis, as well as optimal vaccination strategies, to limit infections.